1980
DOI: 10.3382/ps.0591099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Level Copper Feeding on the Sulfur Amino Acid Need of Chicks Fed Corn-Soybean Meal and Purified Crystalline Amino Acid Diets

Abstract: Supplementation of a corn-soybean meal diet with .05% methionine maximized gain and feed efficiency of three-week-old chicks fed copper at either 0 or 250 mg/kg. With copper present at 500 mg/kg, the supplemental methionine requirement was in excess of .10%. Liver copper stores of chicks fed copper at 250 mg/kg declined linearly as supplemental methionine level increased, but methionine level had no effect on liver copper when chicks were fed 500 mg/kg copper. Liver copper accumulation did not occur in chicks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

1982
1982
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 15 publications
0
5
2
Order By: Relevance
“…However, we were unable to demonstrate that excess supplemental methionine could amelioriate the adverse effects of a Cu toxicity. This does not agree with the recent reports of Maurice (1978, 1979) and Robbins and Baker (1980a). Part of the discrepancy may be explained by the complete SAA adequacy of our basal diet.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, we were unable to demonstrate that excess supplemental methionine could amelioriate the adverse effects of a Cu toxicity. This does not agree with the recent reports of Maurice (1978, 1979) and Robbins and Baker (1980a). Part of the discrepancy may be explained by the complete SAA adequacy of our basal diet.…”
Section: Discussioncontrasting
confidence: 99%
“…The basal diet used in our experiments contained very little supplemental inorganic sulfur. This might explain a portion of the discrepancy between our results and the results of Maurice (1978, 1979), and Robbins and Baker (1980a).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Methionine has been used to treat the toxic symptoms caused by excessive inges tion of Cu in chicks and chelation reactions, which result in less efficient absorption and/or utilisation of Cu, appear to be the protective mechanisms involved [20], Simi larly excessive Cu ingestion can impair me thionine utilization and increase the dietary requirement of chicks for sulfur amino acids [21]. The current work shows clearly that methionine supplementation decreases tis sue Cu levels and the activities of several Cucontaining enzymes in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jensen and Maurice (1979) and Harms (1979, 1984) were able to show that the growth-depressing effect of Cu could be alleviated with supplemental methionine (MET). Robbins and Baker (1980a) demonstrated that supplemental amino acids, minerals, and vitamins could overcome the growth depression observed when chicks were fed 500 mg/kg Cu in a purified diet. These results led Christmas and Harms (1984) to postulate that the growth de- pression observed in chicks fed high levels of Cu may be the result of two separate factors: 1) a nutrient deficiency resulting from reduced feed intake, and 2) Cu toxicosis per se.…”
Section: Introductionmentioning
confidence: 98%